Development of an Automated Battery Voltage Measurement System for Preventive Maintenance Using LabVIEW and MySQL - Karman, Sukarman; Paramacita, Luh (Instrumentasi, 2026)
Manual data recording for battery preventive maintenance (PM) is prone to error and inefficient. This study developed an integrated automated data acquisition system to address these issues. The implemented system utilizes an Arduino Nano with a voltage sensor and Bluetooth module for measurement and wireless transmission. A custom LabVIEW interface receives the data in real-time and provides visualization, while a MySQL database serves as a centralized repository. Testing demonstrated the sensor circuit's high reliability, showing an average measurement error of 0.50% and a Mean Absolute Error (MAE) of 0.01 V. Most significantly, the system reduced the total PM execution time by 24% by eliminating manual transcription and double-entry. This integrated solution presents a practical and cost-effective framework for modernizing PM operations in industrial settings, enhancing both data accuracy and operational efficiency.